Seroprevalence of Chlamydia abortus in camel in the western region of Libya (Journal of Advanced Veterinary and Animal Research, 2016)
Objective: The present study was primarily undertaken to determine the seroprevalnace of Chlamidya abortus infection in the Libyan camel (Camelus dromedarius).Materials and methods: Serological tests for C. abortus antibodies were conducted with 245 camels (205 females and 40 males) in different localities in the western region of Libya. Animals varied in age from